AGRICULTURE AND THE EFFECTIVENESS OF SUPPORT POLICIES IN ALBANIA ON FOCUS: FRUIT PRODUCTION - Dorjan Marku (European Scientific Journal, ESJ, 2015)
This study refers to some very important issues regarding the support policies applied generally on agriculture and mainly on fruit production as a developing strategic sector. It aims to analyze the impact of applied support schemes, for a sustainable agriculture sector and evaluate the development of fruticulture. The application of direct support schemes, aiming to intervene on the improvement of agriculture technology, drainage and irrigation, increased numbers of orchards inventory and storage capacities in order to increase production and quality, it looks to be the main trend of development. The study contributes on the increased knowledge over the impact of actual support schemes in the region and gives recommendations on different options over the effects of agriculture support schemes. The research paper will be conducted based on a detailed review of the available literature, in order to determine clearly the situation of the applied support policies and its effects on the development of agriculture and fruit production.